2022
DOI: 10.1177/23259671221093968
|View full text |Cite
|
Sign up to set email alerts
|

Ligament Augmentation Reconstruction System (LARS) for Ankle Lateral Ligament Reconstruction in Higher-Risk Patients: A 5-Year Prospective Cohort Study

Abstract: Background: The modified Broström-Gould (MBG) procedure is the gold standard for patients with chronic ankle instability (CAI), but it is relatively contraindicated for patients with higher body weight or generalized ligamentous laxity (GLL). The use of the ligament augmentation reconstruction system (LARS) is an alternative. Hypothesis: It was hypothesized that clinical outcomes would be similar in patients with increased body weight (>90 kg) or GLL, relative to controls. Study Design: Cohort study; Level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Extensive literature indicated good clinic efficacy and superiority of ACL reconstruction with LARS ligaments for high fatigue resistance, and biopsies have additionally shown complete cellular and connective tissue ingrowth [ 22 , 23 ]. LARS was also used for ATFL reconstruction in CLAI patients, which got excellent clinic efficacy and achieved good ankle stability compared to the modified Broström repair [ 24 , 25 ]. However, some studies demonstrated that limitations of ATFL reconstruction in ankle activity following and the removal of ATFL remnants can potentially affect ankle functional recovery similar to remnant-preserved anterior cruciate ligament (ACL) reconstruction [ 26 , 27 ], and ATFL remnant preservation was benefit for proprioceptive recovery [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature indicated good clinic efficacy and superiority of ACL reconstruction with LARS ligaments for high fatigue resistance, and biopsies have additionally shown complete cellular and connective tissue ingrowth [ 22 , 23 ]. LARS was also used for ATFL reconstruction in CLAI patients, which got excellent clinic efficacy and achieved good ankle stability compared to the modified Broström repair [ 24 , 25 ]. However, some studies demonstrated that limitations of ATFL reconstruction in ankle activity following and the removal of ATFL remnants can potentially affect ankle functional recovery similar to remnant-preserved anterior cruciate ligament (ACL) reconstruction [ 26 , 27 ], and ATFL remnant preservation was benefit for proprioceptive recovery [ 28 ].…”
Section: Introductionmentioning
confidence: 99%